2003
DOI: 10.1016/s0896-6273(03)00591-9
|View full text |Cite
|
Sign up to set email alerts
|

Slit Stimulation Recruits Dock and Pak to the Roundabout Receptor and Increases Rac Activity to Regulate Axon Repulsion at the CNS Midline

Abstract: Drosophila Roundabout (Robo) is the founding member of a conserved family of repulsive axon guidance receptors that respond to secreted Slit proteins. Here we present evidence that the SH3-SH2 adaptor protein Dreadlocks (Dock), the p21-activated serine-threonine kinase (Pak), and the Rac1/Rac2/Mtl small GTPases can function during Robo repulsion. Loss-of-function and genetic interaction experiments suggest that limiting the function of Dock, Pak, or Rac partially disrupts Robo repulsion. In addition, Dock can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
186
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(193 citation statements)
references
References 41 publications
6
186
0
1
Order By: Relevance
“…Although CrGAP overexpression does not appear to result in a reciprocal phenotype to that observed when CrGAP function is reduced, the apparent antagonism of Robo repulsion is consistent with the observed positive role for rac in regulating midline crossing (14,15,24). To test directly whether CrGAP antagonizes rac, we increased CrGAP levels in embryos expressing the dominant negative Rac, N17Rac.…”
Section: Crgap Overexpression Antagonizes the Repulsive Function Of Rmentioning
confidence: 65%
See 1 more Smart Citation
“…Although CrGAP overexpression does not appear to result in a reciprocal phenotype to that observed when CrGAP function is reduced, the apparent antagonism of Robo repulsion is consistent with the observed positive role for rac in regulating midline crossing (14,15,24). To test directly whether CrGAP antagonizes rac, we increased CrGAP levels in embryos expressing the dominant negative Rac, N17Rac.…”
Section: Crgap Overexpression Antagonizes the Repulsive Function Of Rmentioning
confidence: 65%
“…In rac1, mtl double mutants, axons are misrouted across the midline (14). Biochemical and genetic studies have revealed an important role of Cdc42 and Rac in Robo repulsion (15,16). In contrast to the Slit-dependent negative regulation of Cdc42 in vertebrates, where the Slit͞Robo GAPs (srGAPs) link the Robo cytoplasmic domain directly to Cdc42 (16), how Slit stimulation leads to Rac activation in both vertebrates and Drosophila is unknown.…”
mentioning
confidence: 99%
“…Interaction of srGAP's with the Rho-GTPase, Cdc42 is essential for the repulsive activity of this guidance cue (Wong et al, 2001). Other studies support a role for Phosphatidyl inositol 3 kinase, Dock and Pak, and the Abelson (Abl) kinase and Enabled (Ena) proteins further implicating actin and microtubule reorganization in Slit-Robo signaling (Bashaw et al, 2000;Fan et al, 2003;Wang et al, 2003). Our time-lapse studies showed a change in cell morphology, as the presence of Slit2 aggregates increased the number of noninvading ruffling cells.…”
Section: Discussionmentioning
confidence: 98%
“…Slit stimulation leads to recruitment of a Dock and Pak complex to the Robo receptor and increases Rac activation (Fan et al, 2003). In contrast, Vilse, a conserved family of RhoGAPs, regulate the repellent response to Slit by binding to the intracellular domain of Robo receptors and promoting Rac inactivation (Lundstrom et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation